Theoretical Study of The Life Story Narrative Personality Dynamics Based on Archetype in Indonesian Context Entrepreneurs - Bimo Wikantiyoso; Benedicta Prihatin Dwi Riyanti; Angela Oktavia Suryani (Journal of International Conference Proceedings (JICP), 2019)
Understanding personality development of entrepreneurs is important in current entrepreneurial research. Previous studies have mentioned some perspectives towards a scientific understanding of entrepreneurship, through identification and in-depth examination of personality characteristics. These studies show that individual's function as a totality of personal characteristics (which involve biological, psychological, and cultural levels related to personal narratives) is needed. Some experts point out that success can be explained in the dynamics of the daily journey of the business persons than in trying to explain them into personality categories. The growth of entrepreneurial personality can be understood in accordance with the identity of the community and local culture. The wholeness of a person being an entrepreneur is a process of forming and revealing the development of an entrepreneurial personality. Personality growth will be revealed along the journey of life, following the same pattern in a narrative life story that is influenced by socio-cultural aspects. These patterns can be expressed in archetype. Entrepreneurs also share a set of cultural and social values, some of which are based on the values held by the community. However, research on entrepreneurial personality as a whole in the context of Indonesian culture, is still needed This study aims to look at entrepreneurship as the dynamic’s perspective of the personality narrative life stories and archetype of the cultural context in Indonesia. In addition, this study seeks non-economic factors, such as entrepreneurial personality and culture, affect the dynamics of the performance of a startup business. Through the study of archetype theory and narrative life story, it can be proposed a measuring tool that can explain the concept of entrepreneurial archetype personality in the Indonesian context. This archetype personality measurement tool uses a life story perspective that sees the dynamics of entrepreneurial journey as an archetype hero journey